HUBUNGAN KOORDINASI KESEIMBANGAN TERHADAP HASIL BELAJAR SHOOTING BASKET KELAS VII SMP LKIA PONTIANAK - Apriansyah, Firman; Triansyah, Andika; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractÂ The purpose of this study is to find out how much the combined relationship between coordination and balance to the results of shooting basketball class VII SMP LKIA Pontianak. Special issues to be addressed. 1. How to improve the results of shooting basketball balls on students in class VII of LKIA Junior High School? 2. How much is the combined relationship between coordination and balance to the results of shooting basketball class VII SMP LKIA Pontianak. The method used in this research is to use descriptive method, with research form using correlation or correlation or relationship. The population used in this research is Junior High School, especially son, amounting to 6 students, while the samples used in can through systematic sampling. The samples studied were students who followed extracurricular Basket at SMP LKIA Pontianak. The result of data analysis used in this research is product moment correlation technique. The relationship between coordination and balance with the results of shooting the ball in basketball.Conclusion of the authors in this study showed that between coordination and balance with the results of shooting basketball in class VII Junior Secondary School Institute of Welfare and Childhood in Pontinak, has a significant relationship.Keywords: Basic Skills, Shooting, Ball, Basket, Learners.Â